2019
DOI: 10.1515/med-2019-0059
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive pilonidal sinus treatment: A narrative review

Abstract: AbstractThe management of chronic pilonidal disease remains controversial, but recently, new minimal invasive approaches have been proposed. Whereas in the conventional surgical treatment an elliptical wedge of skin and subcutaneous tissue is created to remove the sinus and its lateral tracks, the basis for our new treatment is to create a minimal elliptical wedge of the subcutaneous tissue, including all the inflamed tissue and debris while leaving the overlying skin intact. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
1
23
0
1
Order By: Relevance
“…Compared to excision and primary closure techniques, EPSiT is a minimally invasive procedure, has a low recurrence rate, and requires a minimal hospital stay. Both sinusectomy and endoscopic approaches to PSD are safe and more effective than conventional techniques 32 . Our report suggests that this surgical approach could be proposed as a first‐line treatment of PSD and, therefore, is worth further study.…”
Section: Discussionmentioning
confidence: 74%
“…Compared to excision and primary closure techniques, EPSiT is a minimally invasive procedure, has a low recurrence rate, and requires a minimal hospital stay. Both sinusectomy and endoscopic approaches to PSD are safe and more effective than conventional techniques 32 . Our report suggests that this surgical approach could be proposed as a first‐line treatment of PSD and, therefore, is worth further study.…”
Section: Discussionmentioning
confidence: 74%
“…The observed preference for fistulectomy in Switzerland may be associated with it first being described by Swiss surgeons [7]. Another minimally invasive technique using video-assisted ablation of PD was described in 2014 in Italy showing promising results [13][14][15]. Nevertheless, VAAPS was not assessed in the present survey.…”
Section: Discussionmentioning
confidence: 87%
“…Other treatments include injection of fibrin glue [10,11] or phenol [4,12] into sinus tracts. Video-assisted ablation of pilonidal sinus (VAAPS) was described in 2014 where sinus cavity ablation and cleaning are minimally invasively performed under videoscopic guidance [13][14][15]. Acute abscess formation is typically treated by incision and drainage.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings compare well with ours. A first systematic review of EPSiT demonstrated high cure rates, low recurrence rates (<5%), high patient satisfaction, and little time off work or school [ 55 ]. However, in the guidelines elaborated by the ASCRS, only a weak recommendation for endoscopic and video-assisted treatment of PSD was made [ 4 ].…”
Section: Discussionmentioning
confidence: 99%